2011
DOI: 10.1038/nature10239
|View full text |Cite|
|
Sign up to set email alerts
|

DMRT1 prevents female reprogramming in the postnatal mammalian testis

Abstract: Sex in mammals is determined in the foetal gonad by the presence or absence of the Y chromosome gene Sry, which controls whether bipotential precursor cells differentiate into testicular Sertoli cells or ovarian granulosa cells1. This pivotal decision in a single gonadal cell type ultimately controls sexual differentiation throughout the body. Sex determination can be viewed as a battle for primacy in the foetal gonad between a male regulatory gene network in which Sry activates Sox9 and a female network invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
505
0
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 593 publications
(539 citation statements)
references
References 31 publications
(53 reference statements)
26
505
0
8
Order By: Relevance
“…1,5 Animal studies have revealed multiple and long-lasting interactions between these male and female pathways; for instance, the loss of Foxl2 or Dmrt1 in murine adult granulosa and Sertoli cells, respectively, results in trans-differentiation to an opposite cell fate. 6,7 Subtle imbalances of this strictly regulated sex-specific gene network can lead to disorders or differences of sex development (DSD). 1 Currently, mutations in genes known to be involved in sex development explain the molecular pathogenesis in only a minority of 46,XY DSD cases.…”
Section: Introductionmentioning
confidence: 99%
“…1,5 Animal studies have revealed multiple and long-lasting interactions between these male and female pathways; for instance, the loss of Foxl2 or Dmrt1 in murine adult granulosa and Sertoli cells, respectively, results in trans-differentiation to an opposite cell fate. 6,7 Subtle imbalances of this strictly regulated sex-specific gene network can lead to disorders or differences of sex development (DSD). 1 Currently, mutations in genes known to be involved in sex development explain the molecular pathogenesis in only a minority of 46,XY DSD cases.…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, DMRT1 was found to be expressed both in Sertoli cells and in germ cells (Lei et al, 2007). Moreover, it was indicated that DMRT1 in Sertoli cells was essential to maintain testis determination (Matson et al, 2011) and regulate tubule morphology, spermatogenesis, and sperm function in mammals (Agbor et al, 2013). Additionally, DMRT1 in spermatogonia was demonstrated to determine whether spermatogonia undergo mitosis and spermatogonial differentiation or meiosis (Matson et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Une publication très récente [38] rapportant l'invalidation spécifique de Dmrt1 dans les cellules de Sertoli renforce la constatation d'une non-conservation de rôles importants de Foxl2 dans l'ovaire et de Dmrt1 dans le testicule chez la souris. Ce travail de l'équipe de David Zarkower publié en Juillet 2011 peut être considéré comme le pendant mâle de l'invalidation à l'âge adulte de Foxl2 dans l'ovaire [6,7].…”
Section: Note Ajoutée Aux éPreuvesunclassified